Knowledge, Attitude, and Practice toward COVID-19 Questionnaire-Indonesian Version - Yafi Sabila Rosyad; Yohanes Andy Rias; Tiur Romatua Sitohang; Pasionista Vianitati; Pembronia Nona Fembi; Raden Surahmat; Nia Desriva (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2021)
Coronavirus disease was detected for the first time since the extraordinary incident in Wuhan, China, in December 2019 and has now spread to 204 countries. COVID-19 is a highly contagious disease. This study aimed to translate the Knowledge, Attitude, and Practice toward COVID-19 Questionnaire and evaluate its validity and reliability Indonesia version. The original was Knowledge, Attitude, and Practice toward COVID-19 Questionnaire translated from English into Indonesian. The reliability scale analysis technique does validity and reliability testing. The question item validity is sawed from the magnitude of r-table value with r-count and reliability seen through Cronbach's alpha coefficiency. This study shows the Knowledge, Attitude, and Practice toward COVID-19 Questionnaire in the context of Indonesian all items of valid and reliable.